2005
DOI: 10.1002/jcu.20092
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically guided core biopsy in the assessment of thyroid nodules

Abstract: Sonographically guided core biopsy provides an accurate and safe alternative to FNAC in the assessment of thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 21 publications
(14 reference statements)
1
75
0
Order By: Relevance
“…Sonographically guided thyroid nodule CB has been shown to be accurate, safe, and well tolerated (15,17,19,(26)(27)(28). There are several theoretical reasons why sonographically guided CB might be useful when thyroid nodule FNA is nondiagnostic: CB can provide more tissue than a nondiagnostic FNA and cellular architecture is retained, facilitating accurate histologic diagnosis (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Sonographically guided thyroid nodule CB has been shown to be accurate, safe, and well tolerated (15,17,19,(26)(27)(28). There are several theoretical reasons why sonographically guided CB might be useful when thyroid nodule FNA is nondiagnostic: CB can provide more tissue than a nondiagnostic FNA and cellular architecture is retained, facilitating accurate histologic diagnosis (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have compared thyroid FNA and CB, [9][10][11][12][13][14][15]28,29 to our knowledge, only 1 study 29 has described the practice of FNA followed by CB in nondiagnostic or suboptimal FNA cases during the same procedure. A few studies have reported higher accuracy with combined FNA/CB than with either procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported higher accuracy with combined FNA/CB than with either procedure alone. 10,11,14 Harvey et al 9 reported that patients who underwent CB had a lower surgery rate compared with patients who underwent FNA (11% vs 43%). Mehrotra et al 15 reported better adequacy with CB than with freehand FNA (inadequate rate of 17.6% vs 34.8%) but did not observe any improvement in accuracy by using CB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fine-needle technique is popular because it is low risk and cytology provides diagnostic information about nuclear and cytoplasmic detail that is not available with a core biopsy. 30 The technique for US-guided fine-needle thyroid biopsy involves three steps: puncture of the nodule or goiter, obtaining the sample, and preparation of the slides. With the surgeon performing the biopsy, results from some studies showed that it is technically feasible, 22 increases adequacy and efficacy, especially with the presence of immediate cytopathology assessment, 24,26 and shortens time for diagnosis of thyroid nodules, which has implications for oncological benefit as well.…”
Section: Fnac = Fine-needle Aspiration Cytologymentioning
confidence: 99%